1994
DOI: 10.1111/j.1365-3040.1994.tb02018.x
|View full text |Cite
|
Sign up to set email alerts
|

Interacting effects of CO2 concentration, temperature and nitrogen supply on the photosynthesis and composition of winter wheat leaves

Abstract: Winter wheat (Triticum aestivum L., cv. Mercia) was grown at two different atmospheric CO2 concentrations (350 and 700 μmol mol−1), two temperatures [ambient temperature (i.e. tracking the open air) and ambient +4°C] and two rates of nitrogen supply (equivalent to 489 kg ha−1 and 87 kg ha−1). Leaves grown at 700 μmol mol−1 CO2 had slightly greater photosynthetic capacity (10% mean increase over the experiment) than those grown at ambient CO2 concentration, but there were no differences in carboxylation efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
60
1
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(69 citation statements)
references
References 33 publications
5
60
1
1
Order By: Relevance
“…It has been tacitly assumed that this is a response to the increased production of sugars. However, starch accumulation also increases dramatically in nitrogen-limited plants (Hocking & Meyer 1991a;Fichtner et al 1993;Delgrado et al 1994). It has recently been shown that the accumulation of starch in nitrogen-limited plants is not merely a consequence of slow growth and accumulation of sugars but is, instead, triggered by signals that derive from nitrate (Scheible et al 1997a(Scheible et al , 1997b.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been tacitly assumed that this is a response to the increased production of sugars. However, starch accumulation also increases dramatically in nitrogen-limited plants (Hocking & Meyer 1991a;Fichtner et al 1993;Delgrado et al 1994). It has recently been shown that the accumulation of starch in nitrogen-limited plants is not merely a consequence of slow growth and accumulation of sugars but is, instead, triggered by signals that derive from nitrate (Scheible et al 1997a(Scheible et al , 1997b.…”
mentioning
confidence: 99%
“…Acclimation is accompanied by alterations in gas exchange characteristics that are indicative of a decreased capacity for carboxylation (Stitt 1991;Sage 1994) and by a decrease of Rubisco activity in tobacco Sicher, Kremer & Rodermel 1994), tomato (Van Oosten, Wilkins & Besford 1994), Arabidopsis (Cheng, Moore & Seeman 1998), Scirpus olneyi (Jacob et al 1995), wheat (Nie et al 1995;Rogers et al 1996b;Sicher & Bunce 1997), barley (Sicher & Bunce 1997), rice (Vu et al 1997), Panicum laxum (Ghannoum et al 1997), loblolly pine (Tissue, Thomas & Strain 1993, 1997, cherry (Atkinson et al (1997), oak (George, Gerant & Dizengremel 1996) and cork oak (Faria et al 1996). Acclimation of photosynthetic rate (Wong 1979;Oberbauer et al 1986;Tissue et al 1993;Pettersson et al 1993;Sage 1994;Pettersson & MacDonald 1994;El-Kohen & Mousseau 1994;Miglietta, Giuntoli & Bindi 1996;Rogers et al 1998) and the decrease of Rubisco activity in elevated [CO 2 ] (Wong 1979;Tissue et al 1993;Delgrado et al 1994;Webber, Nie & Long 1994;Riviere-Rolland, Contard & Betsche 1996;Rogers et al 1996a) is more marked in nitrogen-limited than in nitrogen-sufficient plants.…”
Section: Introductionmentioning
confidence: 99%
“…This is contrary to the findings of the present study, where the addition of L-methionine, irrespective of concentration, produced an inhibitory effect on the leaf chlorophyll content of the CAB-6P rootstock, whereas for the Gisela 6, it had no effect whatsoever. Delgado et al (1994) found that in winter wheat, nitrogen deficiency reduced both the chlorophyll content in the leaves and the activity of RuBisCo, resulting in decreased photosynthetic capacity and carboxylation efficiency. This also applies to the CAB-6P explants in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…According to Delgado et al (1994), adding amino acids to the culture medium as a source of organic N increased both the chlorophyll concentration and photosynthetic activities in the leaves. This is contrary to the findings of the present study, where the addition of L-methionine, irrespective of concentration, produced an inhibitory effect on the leaf chlorophyll content of the CAB-6P rootstock, whereas for the Gisela 6, it had no effect whatsoever.…”
Section: Discussionmentioning
confidence: 99%
“…Assimilation of inorganic nitrogen present within the atmosphere into carbon skeletons is fundamentally important to plant productivity, biomass production and, especially, cultivation income. Nitrogen deficiency in plants is considered to cause a decrease in photosynthetic structural compounds, like chlorophyll and ribulose bisphosphate carboxylase (rubisco), which leads to a reduction in photosynthetic capacity and carboxylation efficiency (Delgado et al, 1994). Nitrogen is used to form glutamine, a precursor of many amino acids, like nucleic acids, alkaloids and polysaccharides, as well as secondary metabolites like polyamines (Bagh et al, 2004).…”
Section: Introductionmentioning
confidence: 99%